ANALISIS AKSI BOIKOT KARIKATUR NABI MUHAMMAD SAW DALAM PERSPEKTIF TEORI KONFLIK DAN TINDAKAN SOSIAL - Fikri Ramdani Firdaus; Supriyono Supriyono (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
Differences are things that often occur between people, both differences of opinion due to different understandings, differences can lead to conflicts within them and can even lead to demonstrations or movements carried out by the masses. . Functional conflict theory assesses the problem of differences in religious values having negative and positive functions. The problem related to the caricature of the Prophet Muhammad is an international conflict because it involves religion and belief. Social action is behavior carried out by individuals by considering interpretive situations, interactions and social relations that are associated with value preferences, beliefs, interests, emotions, power, authority, culture, agreements, ideas, habits or others that are owned by individuals. The research method is a literature study method that describes the results of the analysis of people's writings or observed behavior. The results of the study show that Islamiphobia is an attitude that can be said to be discriminatory by some French people towards Muslim immigrants. The problem related to the caricature of the Prophet Muhammad is an international conflict because it involves religion and belief